2022
DOI: 10.1021/acsaelm.2c00101
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Recent Developments in Ohmic and Schottky Contacts on Ga2O3 for Device Applications

Abstract: Ultrawide bandgap β-gallium oxide (β-Ga2O3) is emerging as a viable candidate for next-generation high-power electronics, including Schottky barrier diodes (SBDs) and field-effect transistors (FETs). This is due to its excellent material properties such as ultrawide bandgap of 4.6–4.9 eV, high breakdown electric field of 8 MV/cm, very high Baliga’s figure of merit (BFOM) and mature technology for large bulk single crystals, and epitaxial techniques with controllable n-type doping. Ohmic and rectifying metal–se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 292 publications
3
40
0
1
Order By: Relevance
“…Subsequent annealing brought a partial restoration of forward current for both fluences, but degradation of the front contact was apparent above 300 • C and prevented further improvement in device performance. This is clearly a result of the Ni/Au interacting with the NiO, since previous studies have shown the rear Ti/Au/Ga 2 O 3 contact is stable under these conditions [40,41]. Control samples that were not irradiated but annealed at the same temperatures confirm the origin of the degradation at 400 • C. The trends in forward density with fluence and annealing temperature are made clearer in the linear plot of figure 4, which shows that annealing alone degrades the forward current for 400 • C anneals.…”
Section: Resultsmentioning
confidence: 84%
“…Subsequent annealing brought a partial restoration of forward current for both fluences, but degradation of the front contact was apparent above 300 • C and prevented further improvement in device performance. This is clearly a result of the Ni/Au interacting with the NiO, since previous studies have shown the rear Ti/Au/Ga 2 O 3 contact is stable under these conditions [40,41]. Control samples that were not irradiated but annealed at the same temperatures confirm the origin of the degradation at 400 • C. The trends in forward density with fluence and annealing temperature are made clearer in the linear plot of figure 4, which shows that annealing alone degrades the forward current for 400 • C anneals.…”
Section: Resultsmentioning
confidence: 84%
“…[85] As a benchmark for print-patterned contacts in Table 1, contact characteristics of high-quality vacuum-processed TFTs have been widely studied. [86][87][88][89][90][91][92][93][94] For example, values as low as ρ c = 10 −5 -10 −3 Ω cm 2 are reported in the literature for IGZO [16,17] and gallium oxide (Ga 2 O 3 ), [47] but the reported range covers several orders of magnitude up to ρ c = 10 Ω cm 2 depending on S/D material. Furthermore, ρ c < 10 −4 Ω cm 2 were found for Ag, In, Ti, ITO, and amorphous IZO (a-IZO) S/D contacts for pulsed laser deposited a-IGZO TFTs, where Ti and ITO formed Ohmic contacts and resulted in better TFTs than devices with Au Schottky-contacts.…”
Section: Contact Resistance and Metricsmentioning
confidence: 99%
“…Contact characteristics have been studied and reviewed for vacuum-processed metal-oxide TFTs. [46][47][48] On the other hand, print-patterned S/D contacts for oxide TFTs are less broadly studied. In recent years, this question has received some attention as evidenced by the reports related to print-patterned S/D electrodes for oxide TFTs shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike commercially available UV PDs based on narrow-band-gap semiconductor materials such as Si and GaAs, they do not require any additional optical filter or large cooling systems. ,− Among these, β-Ga 2 O 3 has received a lot of attention because of its excellent material properties such as an ultrawide direct band gap of about 4.9 eV, superior radiation hardness, high chemical and thermal stability, and high absorption coefficient (>10 5 cm –1 ). In addition, to date, high-crystalline-quality Ga 2 O 3 single-crystal substrates, epilayers, and thin films could be grown quite maturely and cost-effectively by various melt growth and thin-film techniques including edge-defined film-fed growth (EFG), Czochralski (CZ) method, MOCVD, halide vapor-phase epitaxy (HVPE), atomic layer deposition (ALD), pulsed laser deposition (PLD), and molecular beam epitaxy (MBE) without any doping complexity in comparison to other wide and ultrawide-band-gap semiconductor materials. Apart from the β-phase, DUV PDs have also been demonstrated on amorphous and ε-phases of Ga 2 O 3 . ,, …”
Section: Introductionmentioning
confidence: 99%